What is the impact of research champions on integrating research in mental health clinical practice? A quasiexperimental study in South London, UK. Issue 9 (11th September 2017) - Oduola, Sherifat; Wykes, Til; Robotham, Dan; Craig, Tom K J
Abstract : Objectives: Key challenges for mental health healthcare professionals to implement research alongside clinical activity have been highlighted, such as insufficient time to apply research skills and lack of support and resources. We examined the impact of employing dedicated staff to promote research in community mental health clinical settings. Design: Quasiexperiment before and after study. Setting: South London and Maudsley National Health Service Foundation Trust. Participants: 4455 patients receiving care from 15 community mental health teams between 1 December 2013 and 31 December 2014. Outcome measures: The proportion of patients approached for research participation in clinical services where research champions were present (intervention group), and where research champions were not present (comparison group). Results: Patients in the intervention group were nearly six times more likely to be approached for research participation (Adj. OR=5.98; 95% CI 4.96 to 7.22). Conclusions: Investing in staff that promote and drive research in clinical services increases opportunities for patients to hear about and engage in clinical research studies. However, investment needs to move beyond employing short-term staff.